Inequality and dynamics of earnings and disposable income in Denmark 1987-2016 - Søren Leth-Petersen; Johan Sæverud (Quantitative Economics, 2022)
We document facts about earnings and disposable income inequality and growth in Denmark in the period 1987-2016. During this period, the distribution of log earnings growth exhibits skewness that varies with the business cycle and has strong excess kurtosis. Denmark has a progressive income tax system with a high level of taxes and a relatively generous and heavily subsidized unemployment insurance system. Consequently, the dispersion of log disposable income growth is much smaller than for earnings, and the distribution exhibits very limited skewness and much reduced excess kurtosis. These results emphasize the importance of distinguishing between earnings and disposable income when modeling income dynamics, and they suggest that the Danish welfare state plays an important role in reducing the impact of earnings fluctuations on disposable income.
Keywords: D31; H24; J31; 330; Inequality; income dynamics; earnings; disposable income